ABO-incompatible renal transplantation: The journey so far on a road less traveled - Pranaw Kumar Jha; Ashish Nandwani; Ajay Kher; Shyam Bihari Bansal; Sidharth Sethi; Reetesh Sharma; Manish Jain; Dinesh Kumar Yadav; Dinesh Bansal; Rajan Duggal; Rajesh Ahlawat; Vijay Kher (Indian Journal of Transplantation, 2018)
Introduction: ABO-incompatible (ABOi) renal transplant is the only option for patients who have neither blood group-compatible donors nor a suitable swap available. Published Indian experience of ABOi transplants has been far and few. Materials and Methods: This study was conducted across two different centers. All the consecutive ABOi renal transplants performed from November 2011 onward and who had completed at least 6 months of follow-up were included. Data were accessed retrospectively from the medical records. Results: There were fifty ABOi recipients who had completed at least 6 months of follow-up. Most common recipient blood group was group O. Median baseline antiblood group antibody titer (immunoglobulin G) was 256. Patient and death-censored graft survival were 94% and 88%, respectively, and biopsy-proven acute rejection was 22%. Acute antibody-mediated rejection was seen in 8% of the patients. Mean serum creatinine was 1.12 mg/dl at 1-month posttransplant and infection rate was 22%. Conclusion: The outcomes of ABOi transplant were acceptable and it should be promoted to bridge the demand and supply gap for renal transplant and expand the living donor pool.